Is there a Conflict Between General Digitalization and Sustainability and Humanity? - Manfred, Doepp, (European Journal of Applied Sciences, 2025)
We are in a development phase in which analogue subjects such as humans and nature are increasingly being replaced by the technology of digitalization. Analog scalar waves are natural, digital Hertzian waves are unnatural, but they have conquered the market for themselves. Analog products of life are increasingly disappearing. This raises the question of durability and reparability, where analog products are superior. Consumption of resources and limited recycling options create a conflict between digitalization and sustainability. We should save or revive as many analogue products as possible for the benefit of people and nature, because a fully digitalized world would not only be unnatural, but also inhumane.